Мохнатая азбука - Заходер Б. В. (Любимые книги детства, 2005)
Экземпляры: Ф. 11 (20200702) / Инвентарный номер: 45167 / Цена: 33.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: З-38 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44